Landmark based shape variation of normal male, female and sex-reversed tilapia (Oreochromis niloticus) in Bangladesh - Moushomi, R; Saha, S (Progressive Agriculture, 2015)
The truss network systems constructed with the help of landmark were evaluated to infer the shape of normal male, female and monosex male tilapia. A total of sixty (60) individuals from different sources (Subarna Agro Based Initiative and BismillahAgro Production) were collected during September-December, 2013. All the data of the studied characteristics were obtained using the digital photograph of the samples which were analyzed through professional image measurement software. Nine morphometric and eight meristic characters were considered along with twenty six truss network measurements. Highly significant difference (P<0.05) was observed in six (SL, HL, PrDL, MBH, EL and PL) of eight morphometric measurements. In case of truss measurements 7 of 26 measurements showed highly significant differences among the groups. For both morphometric and landmark measurements the first DF accounted for 98.9% and 85.7% and the second DF accounted for 1.1% and 14.3% respectively. With truss network system 100% monosex male samples, 85.5% of normal male samples, 100% of female samples were correctly classified. In both cases, plotting discriminant functions revealed high isolation of the groups especially between the monosex groups with the other two groups. The results showed that the shape of the tested tilapia groups significantly differed from each other depending on the truss measurements. that could be explained by the genetic sex related reasons. Progressive Agriculture 26 (2): 168-172, 2015